Spatial patterns of summer demersal fish assemblages around the Antarctic Peninsula and South Shetland Islands - Llompart, Facundo Manuel; Delpiani, Sergio Matias; Lattuca, María Eugenia; Delpiani, Gabriela Elina; Cruz Jiménez, Adriana Milena; Orlando, Paula; Ceballos, Santiago Guillermo; Diaz de Astarloa, Juan Martin; Vanella, Fabián Alberto; Fernandez, Daniel Alfredo (Antarctic Science)
During the research programme conducted on the OV Puerto Deseado in the summers of 2011 and 2013, 36 stations were sampled using a demersal net at depths between 53–590 m in the Antarctic Peninsula and South Shetland Islands. A total 3378 fish specimens belonging to 36 species were recorded. Notothenidae was the best-represented family in species number, with Lepidonotothen nudifrons, L. larseni and Trematomus scotti being the most numerous species. Of the fish assemblages, 20% of the species were considered as dominant, 10% as common, 13% as occasional and 57% as rare. Six groups (and two sub-groups) were obtained by the ordination diagram based on geographical location: group 1=Gerlache Strait, group 2=Deception Islands, group 3=Biscoe Island, group 4=between Elephant and King George islands, group 5=northern Antarctic Peninsula, and group 6=South Shetland Islands, with sub-groups 6a shallower South Shetland Islands and 6b deeper South Shetland Islands. Sampling depth and water temperature significantly explained the spatial pattern. A latitudinal pattern of decreasing abundance from north-east to south-west was found in L. larseni and the opposite in T. scotti. The predictability of fish composition in the assemblages’ areas could be a useful tool for ecosystem-based management. Fil: Llompart, Facundo Manuel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego; Argentina Fil: Delpiani, Sergio Matias. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Mar del Plata. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Lattuca, María Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Delpiani, Gabriela Elina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Mar del Plata. Instituto de Investigaciones Marinas y Costeras; Argentina ...